Size dependent free vibration and buckling of multilayered carbon nanotubes reinforced composite nanoplates in thermal environment. Issue 4 (3rd April 2022) - Daikh, Ahmed Amine; Bachiri, Attia; Houari, Mohamed Sid Ahmed; Tounsi, Abdelouahed
Abstract: In this contribution, we analyze buckling and free vibration of simply-supported cross-ply/angle-ply single-walled carbon nanotubes reinforced composite CNTRC laminated nanoplates in thermal environment. The nonlocal strain gradient theory within the third-order shear deformation plate theory are adopted to capture the size-dependent effects of CNTRC laminated nanoplates. Several types of reinforcement material distributions, a uniform distribution and functionally graded distributions, are inspected. Material properties are temperature-dependent and performed using Touloukian principal. The influence of CNTs reinforcement patterns, composite structure, nonlocal parameter, length scale parameter, carbon nanotubes orientation, and the geometric parameters on buckling loads and natural frequencies is examined.